RELATIONSHIPS BETWEEN NUTRIENT ENRICHMENT AND THE PHYTOPLANKTON COMMUNITY AT AN ANDEAN OLIGOTROPHIC LAKE: A MULTIVARIATE ASSESSMENT - E. Fontúrbel, Francisco (2011)
Phytoplankton is one of the groups most sensitive to eutrophic conditions, and its disturbance has a potential negative bottom-up effect on lentic ecosystems. In this research we used a multivariate statistics approach (Canonical Correspondence Analysis with a Monte Carlo permutational test) to assess the relationships between nutrient enrichment and the phytoplankton community diversity. Four locations with different levels of eutrophication were sampled at the Bolivian sector of Lake Titikaka. Phytoplankton richness ranged from eight to 16 genera, varying significantly among sites, and its diversity was significantly correlated to nitrogen, phosphorus, and pH (Monte Carlo test, p < 0.05). Phosphorus was determined to be the limiting nutrient in the ecosystem. Community structure assessment showed a non-aggregated distribution of genera among study sites, with few abundant genera, and a BDG analysis pointed to a log-series distribution, suggesting a non–fully random niche partition. The methodological approach used here allowed a rapid assessment of the nutrient enrichment effect considering phytoplankton and nutrients as a whole, which is a more powerful approach than studying single-nutrient or singlegroup relationships with univariate procedures.